IMPLICATIONS OF THE COVID-19 PANDEMIC ON FOREIGN DIRECT INVESTMENT IN EUROPEAN TRANSITION ECONOMIES - Tubić Ćurčić, Tijana (Economic Outlook, 2022)
In early 2020, the world faced a serious crisis caused by the Covid-19pandemic, and the application of restrictive measures to prevent and slow down thespread of the virus had a negative impact on economic flows, including foreign directinvestment (FDI). The effects of the Covid-19 pandemic on global FDI flows have beendevastating, resulting in a large drop in FDI. Flows to European transition countrieshave also been affected, but less than the world average. It is expected that the recoveryof FDI from the shock of 2020 would be long and that it would be impossible to return tostructural and geographical patterns before the pandemic. Having in mind the above,the aim of this paper was to analyze the dynamics of FDI before and during thepandemic in European transition countries in order to examine the effect of Covid-19pandemic on FDI. The results of the research confirm the negative impact of thepandemic on the flows of FDI in European transition economies, except for Montenegro,Bulgaria, Hungary and Estonia, where an increase in the inflow of FDI was determined.
Keywords: Foreign direct investment; Covid-19 pandemic; European transition economies